The Strategy of Housing Rehabilitation and Reconstruction after 2022 Earthquake in Cianjur, West Java, Indonesia - Winda Dwi Aryani; Sobar Sutisna (CV. AFDIFAL MAJU BERKAH, 2023)
Monday, November 21st, 2022 at 13.21.10 WIB the Cianjur Regency area was rocked by a tectonic earthquake with a magnitude of M-5.6. The epicenter was located in the source zone of an active fault earthquake which had not been mapped before and it was recently identified that the earthquake was caused by the Cugenang Fault. The earthquake resulted in 335 fatalities, 8 people were missing, and 59,889 houses were damaged. After the emergency response steps were taken, further measures taken were post-disaster rehabilitation and reconstruction activities so that community activities could recover quickly, including the recovery of the housing and settlement sector. Therefore, the Government launched a post-disaster recovery program by providing program and budget support for the rehabilitation and reconstruction of housing and settlements. The purpose of this research is to analyze the strategy for the rehabilitation and reconstruction of the housing and settlement sector affected by the Cianjur earthquake. This research is a qualitative research with a literature study approach where the data comes from books, journals, regulations, documentation and other literature. The results showed that the strategy for the rehabilitation and reconstruction of the housing sector was carried out using two mechanisms, namely 1) stimulant financial assistance for housing repairs carried out in-situ using the community empowerment method and 2) relocating houses affected by disasters which were carried out ex-situ using the contractual method. This research is a qualitative research with a literature study approach where the data comes from books, journals, regulations, documentation and other literature. The results showed that the strategy for the rehabilitation and reconstruction of the housing sector was carried out using two mechanisms, namely 1) stimulant financial assistance for housing repairs carried out in-situ using the community empowerment method and 2) relocating houses affected by disasters which were carried out ex-situ using the contractual method. This research is a qualitative research with a literature study approach where the data comes from books, journals, regulations, documentation and other literature. The results showed that the strategy for the rehabilitation and reconstruction of the housing sector was carried out using two mechanisms, namely 1) stimulant financial assistance for housing repairs carried out in-situ using the community empowerment method and 2) relocating houses affected by disasters which were carried out ex-situ using the contractual method.